Synthesis and Characterization of Novel Azo Compounds Derived from Sulfamethoxazole: Optical, Thermal, and Antimicrobial Investigations - Shawkat, Safa Mahmood; Salman, Maha M.; Jassim, Luma Abbas (American Journal of Biomedicine and Pharmacy, 2026)
Background: Azo compounds are an important class of organic materials with widespread applications in optoelectronics, dye-sensitized solar cells, and medicinal chemistry. Methods: Three novel azo derivatives (Azo-1, Azo-2, Azo-3) were synthesized via diazotization of sulfamethoxazole followed by coupling with 2-naphthol, resorcinol, and 8-hydroxyquinoline, respectively. Compounds were fully characterized by FT-IR, ¹H/¹³C NMR, UV-Vis spectroscopy, elemental analysis, TGA, DSC, and DFT calculations at B3LYP/6-31G(d,p). Results: Pure products were obtained in 78–86% yield. Azo-1 displayed the most red-shifted absorption (λmax = 485 nm, ε = 18,400 L·mol⁻¹·cm⁻¹); all compounds showed positive solvatochromism and Tonset > 280 °C. Azo-3 exhibited the most potent antimicrobial activity (MIC = 16 µg/mL vs. S. aureus), two-fold less potent than Amoxicillin (MIC = 8 µg/mL). Conclusions: The structure–property relationships established provide a rational basis for designing multifunctional azo-based materials.